Enhanced corrosion resistance of calcium carbonate coatings on magnesium alloy via simple stearic acid treatment - Tianxiao Wang; Panpan Li; Yunting Guo; Yingchao Xu; Wen Kou; Guangyu Li; Jianshe Lian (Journal of Magnesium and Alloys)
Magnesium alloy is a promising biodegradable metal material for hard tissue engineering. However, its high corrosion rate limits its application. In our previous study, we biomimetically deposited a calcium carbonate coating on the surface of magnesium alloy using siloxane induction. This calcium carbonate coating demonstrated excellent in vitro biocompatibility and provided partial protection for the magnesium alloy substrate. In this study, we further enhanced the corrosion resistance of the calcium carbonate coating by treating it with stearic acid and its derivative, sodium stearate. Electrochemical corrosion tests revealed that the sodium stearate-treated calcium carbonate coating reduced the corrosion rate by two orders of magnitude. Additionally, in vitro biocompatibility assessments showed that while the biocompatibility of the sodium stearate-treated coating was slightly reduced, it remained acceptable compared to the magnesium substrate. This study builds on our previous work and offers a promising reinforcement strategy for degradable magnesium alloys in medical applications.